"Gueule cassée" (facial injuries): a 3D paleotraumatology study and facial approximation of a Napoleonic soldier who died in 1812 at Königsberg during the Russian Campaign. (27th December 2018) - Coutinho Nogueira, Dany; Dutailly, Bruno; Comte, Florent; Vasil'iev, Alexandr; Khokhlov, Alexandr; Shvedchikova, Tatiana; Berezina, Natalia; Buzhilova, Alexandra; Dutour, Olivier; Coqueugniot, Hélène
Abstract: The invasion of Russia by the Napoleonic Grande Armée was a complete disaster. The French army was decimated during the retreat from Russia. Thousands of victims were buried in mass graves located near several cities during the retreat. One of these mass graves was discovered in in the centre of Kaliningrad (formerly Königsberg), presently the most occidental oblast of the Russian Federation. Some skeletons revealed evidence of violence related traumatic injuries. Among them, the skeleton C2 belonged to a young male, who had suffered a serious injury to the lower face. The state of post‐traumatic remodelling indicated survival of about 2 months (between more than 6 weeks and less than 3 months). The 3D reconstruction of the mandible and the maxilla contributed additional information about the injury, its cause, and treatment. This permitted pretraumatic reconstruction of the viscerocranium and mandible through the application of two new techniques: virtual osteotomy and virtual bone transplant from another individual and perform an approximation of the face (to recreate the soft tissues) of this unidentified soldier using anthropological facial approximation in three dimensions software. These results highlight the use of 3D methods in paleopathology and forensic anthropology to reconstruct traumatic facial injuries and the pretraumatic facial appearance.